Glycocaulis profundi sp. nov., a marine bacterium isolated from seawater of the Mariana Trench. Issue 2 (1st November 2019) - Sun, Hao; Hu, Yuyao; Zhou, Shun; Zheng, Yanfen; Zhang, Xiao-Hua
Abstract : A Gram-stain-negative, strictly aerobic, rod-shaped bacterium, without flagellum and designated ZYF765 T, was isolated from seawater sampled at a depth of 4000 m in the Mariana Trench. Strain ZYF765 T grew with 1–15 % (w/v) NaCl (optimum, 4 %), at 16–37 °C (28 °C) and at pH 6.0–10.0 (pH 7.0–8.0). Phylogenetic analysis based on 16S rRNA gene sequences indicated that strain ZYF765 T formed a lineage within the family Hyphomonadaceae, and was distinct from the most closely related species Glycocaulis abyssi, Glycocaulis albus and Glycocaulis alkaliphilus with 16S rRNA gene sequences similarities ranging from 98.42 to 98.63 %. The major respiratory quinone was ubiquinone-10 (Q-10). The polar lipids comprised three unidentified glycolipids, one unidentified aminophospholipid, one unidentified phospholipid and one unidentified aminolipid. The predominant fatty acids (more than 10 % of total fatty acids) were C18 : 1 ω7 c (46.2 %) and C18 : 0 (14.1 %). The DNA G+C content was 67.7 mol%. On the basis of the results of polyphasic taxonomic analysis, strain ZYF765 T is considered to represent a novel species within the genus Glycocaulis, for which the name Glycocaulis profundi sp. nov. is proposed. The type strain is ZYF765 T (=JCM 33028 T =MCCC 1K03554 T ).